Traiettorie tecniche e Metodologia QWERTY: come si applicano alle innovazioni farmaceutiche - Altagracia, Marina; Cimoli, Mario; Kravzov, Jaime; Castillo, Rafael; Espejo, Ofelia; Wertheimer, Albert I. (Farmeconomia. Health Economics and Therapeutic Pathways, 2001)
Hypertension is a problem that has a social component and a biological one. The history of the biological solutions has been an increase in research activities and an increase in the number of new products introduced in the pharmaceutical market and adopted as usual therapies. This article analyzes each of the main innovations in the treatment of moderate arterial hypertension and their competitive inter-relationships using a conceptual frame based on the recent theory of innovation. These innovations compete with each other for a market, similar to what happens with other areas and products. The concept of trajectories and the analysis of the competition process among them has not previously been applied to a pharmaceutical market and offers an exciting new avenue for insurance organizations, government health agencies, provider groups, and manufacturers to analyze trends and events in an organized and consistent framework. Learning by using, pharmacological interrelatedness, and pharma-institutional networks are the main analytical tools used to explain the competing processes among the different trajectories considered.